Age-specific differences in patient reported outcomes among adults with atherosclerotic cardiovascular disease: Medical expenditure panel survey 2006-2015 - Victor Okunrintemi; Eve-Marie A. Benson; Ouassim Derbal; Michael D. Miedema; Roger S. Blumenthal; Martin Tibuakuu; Oluseye Ogunmoroti; Safi U. Khan; Mamas A. Mamas; Martha Gulati; Erin D. Michos (Elsevier, 2020)
Objective: The prevalence of atherosclerotic cardiovascular disease (ASCVD) in younger adults has increased over the past decade. However, it is less well established whether patient reported outcomes differ between younger and older adults with ASCVD. We sought to evaluate age-specific differences in patient reported outcomes among adults with ASCVD. Methods: This was a retrospective cross-sectional survey study. We used data from the 2006-2015 Medical Expenditure Panel Survey (MEPS), a nationally representative sample of the United States population. Adults ≥18 years with a diagnosis of ASCVD, ascertained by ICD9 codes or self-reported data, were included. Logistic regression was used to compare self-reported patient-clinician communication, patient satisfaction, perception of health, emergency department (ED) visits, and use of preventive medications (aspirin and statins) by age category [Young: 18-44, Middle: 45-64, Older: ≥65 years]. We used two-part econometric modeling to evaluate age-specific annual healthcare expenditure. Results: There were 21,353 participants included. Over 9000 (42.6%-weighted) of the participants were young or middle aged, representing ~9.9 million adults aged <65 years with ASCVD nationwide. Compared with older adults, middle-aged and young adults with ASCVD were more likely to report poor patient-clinician communication [OR 1.73 (95% CI 1.28-2.33) and 2.49 (1.76-3.51), respectively], poor healthcare satisfaction, and poor perception of health status, have increased ED utilization and were also less likely to be using aspirin and statins. The mean annual healthcare expenditure was highest among middle-aged adults [$10,798 (95% CI, $10,012 to $11,583)]. Conclusion: Compared with older adults, younger adults with ASCVD were more likely to report poor patient experience and poor health status and less likely to be using preventive medications. More effort needs to be geared towards understanding the age-specific differences in healthcare quality and delivery to improve outcomes among high-risk young adults with ASCVD.